2003
DOI: 10.1007/s00018-003-3133-5
|View full text |Cite
|
Sign up to set email alerts
|

The causes of Charcot-Marie-Tooth disease

Abstract: Charcot-Marie-Tooth (CMT) disease serves as the summary term for the most frequent forms of inherited peripheral neuropathies that affect motor and sensory nerves. In the last 12 years, 14 genes have been identified that cause different CMT subforms. The genes found initially are predominantly responsible for demyelinating and dysmyelinating neuropathies. Genes affected in axonal and rare forms of CMT have only recently been identified. In this review, we will focus on the currently known genes that are associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 185 publications
0
25
0
1
Order By: Relevance
“…Alteration in PMP-22 represent 70% of myelinopathy (Young et al, 2003), in demyelinating human peripheral fibers, we observed axonal sprouting consequently with the lack of inhibitory effect of myelin and normal Schwann cell (Shen et al, 1998;De Bellard et al, 1996). This axonal growing is in close relation with structural and functional changes, as observed among myelin disassembly, axonal sprouting.…”
Section: Schwann Cells' Ribosomes Are Involved In Axonal Sprouting Ofmentioning
confidence: 53%
“…Alteration in PMP-22 represent 70% of myelinopathy (Young et al, 2003), in demyelinating human peripheral fibers, we observed axonal sprouting consequently with the lack of inhibitory effect of myelin and normal Schwann cell (Shen et al, 1998;De Bellard et al, 1996). This axonal growing is in close relation with structural and functional changes, as observed among myelin disassembly, axonal sprouting.…”
Section: Schwann Cells' Ribosomes Are Involved In Axonal Sprouting Ofmentioning
confidence: 53%
“…CMT has been classified into two types, the demyelinating form and the axonal form. At present, at least 11 different genes have been identified as causing demyelinating CMT, including autosomal dominant, autosomal recessive and X-linked types (Young and Suter 2003). Similar clinical manifestations are observed in patients carrying mutations in different genes, while variable presentations are present even in patients with an identical mutation in the same gene.…”
Section: Introductionmentioning
confidence: 98%
“…At present, at least 11 different genes have been identified as causing demyelinating CMT, including autosomal dominant, autosomal recessive, and X-linked types (Young and Suter 2003). To identify the responsible gene mutation, we previously examined 143 Japanese demyelinating CMT patients for autosomal dominant CMT type 1 (CMT1) or X-linked CMT genes including a duplication of 17p11.2-p12 and mutations of peripheral myelin protein 22 (PMP22), myelin protein zero (MPZ), connexin 32 (Cx32), early growth response 2 (EGR2), and lipopolysaccharide-induced tumor necrosis factor-a factor (LITAF) genes (Young and Suter 2003;Street et al 2003). However, we were unable to identify the responsible mutation in 66 (46%) of 143 Japanese demyelinating CMT patients.…”
Section: Introductionmentioning
confidence: 99%